2023
DOI: 10.1021/acs.chemmater.2c03592
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Salt-Inclusion Chalcogenides for Ion Exchange, Photoluminescence, and Scintillation

Abstract: Salt-inclusion chalcogenides (SICs) consisting of covalent and ionic building blocks have emerged as functional materials exhibiting novel topologies that result from the combination of the chalcogenide-based frameworks and the salt inclusions contained within them. Nine compositions of a novel family of SICs [Cs6 X]AGa6 Q 12 (A = Na, K, and Rb; X = F, Cl, and Br; Q = S and Se) were synthesized via halide/polychalcogenide flux crystal growth and structurally characterized. Ex situ powder X-ray diffraction anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 133 publications
0
8
0
Order By: Relevance
“…(left) Schematic classification of salt-inclusion materials by covalent and ionic framework dimensionality. (right) Examples of hybrid materials with 0D-0D, [Cs 6 Cl] 2 Cs 5 Ga 15 Ge 9 Se 48 , 2D-2D, [Na 2 Cl]­Ga Q 2 , 2D-0D, [Cs 6 X ] A Ga 6 Q 12 , frameworks and salt-inclusion fragment dimensionalities, respectively. Gray and green shapes represent covalent and ionic moieties, respectively.…”
Section: Exploratory Flux Crystal Growth Of Chalcogenides Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…(left) Schematic classification of salt-inclusion materials by covalent and ionic framework dimensionality. (right) Examples of hybrid materials with 0D-0D, [Cs 6 Cl] 2 Cs 5 Ga 15 Ge 9 Se 48 , 2D-2D, [Na 2 Cl]­Ga Q 2 , 2D-0D, [Cs 6 X ] A Ga 6 Q 12 , frameworks and salt-inclusion fragment dimensionalities, respectively. Gray and green shapes represent covalent and ionic moieties, respectively.…”
Section: Exploratory Flux Crystal Growth Of Chalcogenides Materialsmentioning
confidence: 99%
“…Therefore, this study revealed a novel synthetic route for obtaining new compositions of SIC materials that cannot be synthesized through the traditional synthetic pathway, highlighting that SCSC transformation generally increases the stabilization range for the kinetic products. Furthermore, complete SCSC anion exchange and partial cation exchange were demonstrated in the example of the [Cs 6 X ] A Ga 6 Q 12 (X = F, Cl, and Br; A = Na, K, and Rb; Q = S and Se) SIC family consisting of a 2D framework and a 0D salt-inclusion moiety, [Cs 6 X ] 5+ . The interesting result was the formation of the fluoride-based SIC [Cs 6 F]­NaGa 6 S 12 via postsynthetic modification of [Cs 6 Cl]­NaGa 6 S 12 using an CsF/CsI flux at 600 °C .…”
Section: Single-crystal-to-single-crystal Postsynthetic Modification ...mentioning
confidence: 99%
See 1 more Smart Citation
“…30 Another example is the [Cs 6 X]AGa 6 Q 12 family consisting of 0D Cs 6 X and 2D gallium chalcogenide units. 31 Heterolayered compositions are structurally similar to salt-inclusion materials, as separate layers may be constructed from cation- and anion-centered polyhedra. For example, in [MO]CuQ (M = Bi and La; Q = S, Se, and Te), where the layered slabs consist of OM 4 and CuQ 4 tetrahedra.…”
mentioning
confidence: 99%
“…We were not able to obtain the [Na 2 Br]GaS 2 analog; changing NaCl to NaBr in the synthesis resulted in the formation of NaGaS 2 . Moreover, we probed ion-exchange reactions that previously demonstrated strong potential as being one synthetic approach for obtaining new compositions of 0D salt-inclusion materials that cannot be prepared directly; 31 however, our attempts to synthesize [Na 2 Br]GaS 2 (see ESI† for more information) using this approach did not succeed. In summary, the t -[Na 2 Cl]GaS 2 composition is the most stable of the t -[A 2 X]GaS 2 (A = Li, Na, and K; X = F, Cl, and Br) compositions based on their decomposition enthalpies (Fig.…”
mentioning
confidence: 99%